2011
DOI: 10.1021/jp109032h
|View full text |Cite
|
Sign up to set email alerts
|

A Compositional Window of Kinetic Stability for Amphiphilic Polymers and Colloidal Nanorods

Abstract: Amphiphilic polymers are often used to disperse nanoparticles in aqueous solution. Polymer adsorption theory predicts that there exists a narrow compositional range of hydrophobic groups on the polymer chain that allows for kinetic stabilization. Too few groups limit polymer adsorption, while too many allow aggregation of polymer-coated nanoparticles for lack of entropic repulsion. We experimentally validate and mathematically describe the existence of this compositional range, and the resulting stability “win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…A content of 13.6 wt% was chosen based on predictions from a model constructed by Jeng et al and empirical renement. 34 Each absorption peak represents the individual (n,m) species of SWNTs. 37,38 The degree to which SWNTs were individualized could be discriminated by the resolution of each peak, i.e.…”
Section: Suspension Ability Of P-dextranmentioning
confidence: 99%
See 1 more Smart Citation
“…A content of 13.6 wt% was chosen based on predictions from a model constructed by Jeng et al and empirical renement. 34 Each absorption peak represents the individual (n,m) species of SWNTs. 37,38 The degree to which SWNTs were individualized could be discriminated by the resolution of each peak, i.e.…”
Section: Suspension Ability Of P-dextranmentioning
confidence: 99%
“…In addition, this preparation scheme utilizing P-dextran does not require ultra-centrifugation and therefore reduces the time and cost of SWNT preparation, which can be scaled up to an industrial level. We previously reported that P-dextran effectively adsorbs onto SWNT surfaces 34 and maintains a stable SWNT suspension without forming bundles when it replaces SC through dialysis. 33 Herein, we explored the ability of P-dextran to suspend SWNTs by direct suspension, forming a P-dextran-SWNT system, using sonication.…”
Section: Introductionmentioning
confidence: 99%
“…al. [ 25 ] These results indicate that phenoxylated dextran strongly binds to the SWNT surface due to the phenoxylated dextran aromatic groups and not easily detach from SWNT surfaces, enabling high colloidal stability of pD-SWNT even in the blood stream of human body, which will be discussed in the later part of this study. Figure 2 d represents UV-vis-NIR absorption spectra of pD-SWNT dispersed in water together with those of SDS-SWNT (Figure 2 c) as a reference.…”
Section: Characterization Of Pd-swntmentioning
confidence: 75%
“…[23,[34][35][36] Open circuit voltage (V oc ) is an important parameter for evaluating the performance of organic solar cells. Traditional B3LYP [32,37] and long range corrected (LRC) functionals CAM-B3LYP [36,38] and tunable ωB97X [39] with 6-311+G(d) basis sets were used to calculate open circuit F I G U R E 1 Chemical structure of SubPC and subAPPCs with one, two, and three six-membered rings: C1, C2, and C3 voltage. B3LYP is the most common density functional used to calculate ground state and local excited states.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this section, the UV-Vis spectra of subPC and subAPPCs are showed in Figure 5 and Table 2. For simplicity and clarity, we only list the results of ωB97X functional because it has an optimized parameter ω for every molecule and the HOMO energy generated with tuned ωB97X [39] functional matches well with the IP of a molecule. [42,53] Besides, B3LYP is a traditional density functional and CAM-B3LYP is not tunable.…”
Section: Uv-vis Spectramentioning
confidence: 99%